HMGB1 Acts in Synergy with Lipopolysaccharide in Activating Rheumatoid Synovial Fibroblasts via p38 MAPK and NF-κB Signaling Pathways - Zheng-Wen He; Yang-Hua Qin; Zhi-Wei Wang; Yan Chen; Qian Shen; Sheng-Ming Dai (Mediators of Inflammation)
Synovial fibroblasts (SF) play a central role in the inflammatory and destructive process in rheumatoid arthritis (RA). High-mobility group box chromosomal protein 1 (HMGB1) or lipopolysaccharide (LPS) alone failed to induce significant changes in proliferation of cultured SF from RA patients, but premixed HMGB1 with LPS (HMGB1-LPS) significantly facilitated SF proliferation. HMGB1 alone failed to induce IL-6, MMP-3, and MMP-13 production in cultured SF but greatly enhanced LPS-induced expression of IL-6, MMP-3, and MMP-13 at both mRNA and protein levels. HMGB1-LPS synergistically upregulated TLR4 and receptor for advanced glycation endproducts (RAGE) expression on the surface of SF. Both blockers of TLR4 and RAGE significantly inhibited the synergistic effects of HMGB1-LPS on the production of IL-6 and MMPs, but blocking antibodies to TLR2 failed. HMGB1-LPS synergistically increased intracellular levels of phosphorylated p38 and phosphorylated IκB. Furthermore, both NF-κB inhibitor Bay11-7085 and p38 inhibitor SB203580 significantly suppressed the enhanced production of IL-6 and MMPs induced by HMGB1-LPS. In conclusion, HMGB1 acts in synergy with LPS to upregulate TLR4 and RAGE expression on the surface of SF in RA and then to augment IL-6, MMP-3, and MMP-13 production, which depends on p38 MAPK and NF-κB activation.